2010
DOI: 10.1007/s10753-010-9186-3
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Valnemulin on Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: Valnemulin reportedly regulates inflammatory responses in addition to its in vitro antibacterial activity. In this study, we established a mouse model of lipopolysaccharide (LPS)-induced inflammatory lung injury and investigated the effect of valnemulin (100 mg/kg) on acute lung injury (ALI) 8 h after LPS challenge. We prepared bronchoalveolar lavage fluid (BALF) for measuring protein concentrations, cytokine levels, and superoxidase dismutase (SOD) activity, and collected lungs for assaying wet-to-dry weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…These are the primary multifunctional cytokines produced from inflammatory cells that exacerbate the extent of lung injury [41]. As in previous studies [42,43], our results showed that the expressions of TNF-α, IL-6 and IL-1ß were significantly increased in BAL fluid after LPS administration as compared to control group, whereas administration of imatinib or nilotinib significantly downregulated the expression of these cytokines as compared to the LPS group.…”
Section: Discussionsupporting
confidence: 86%
“…These are the primary multifunctional cytokines produced from inflammatory cells that exacerbate the extent of lung injury [41]. As in previous studies [42,43], our results showed that the expressions of TNF-α, IL-6 and IL-1ß were significantly increased in BAL fluid after LPS administration as compared to control group, whereas administration of imatinib or nilotinib significantly downregulated the expression of these cytokines as compared to the LPS group.…”
Section: Discussionsupporting
confidence: 86%
“…Despite recent advances in critical care and significant efforts invested in the basic research and clinical trials of ALI, its mortality rate (35%-45%) had remained relatively unchanged since [2]. The inflammatory process played a key role in the development of ALI, and the main pathological change of ALI was acute leakage inflammatory response with leakage of protein into the alveolar space, inflammatory cells accumulation, interstitial edema, and disruption of epithelial integrity [3]. Therefore, it was significant that anti-inflammatory drugs were used to reduce lung injury at early stage of ALI.…”
Section: Introductionmentioning
confidence: 99%
“…Some antibacterial agents not only could regulate immune and inflammatory responses but also possessed antibacterial activity [23]. Valnemulin was proved to have effect on the inflammatory responses for the treatment of LPS-induced acute lung injury (ALI) in mice besides antibacterial activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…At three days after treatment, TNF-α, IL-6, and MCP-1 in the serum of the amphenmulin treatment group were significantly decreased than those of the infection group (p < 0.05). It has been reported that valnemulin can inhibit TNF-α and IL-6 released by macrophages induced by lipopolysaccharide, indicating that valnemulin has certain anti-inflammatory effect [23]. For both valnemulin and amphenmulin were pleuromutilin derivatives, we are wondering whether amphenmulin could possess anti-inflammatory effect like valnemulin.…”
Section: The Therapeutic Effect In An Experimental Model Of Mrsa Wounmentioning
confidence: 99%